Transformation of the Tanning Handicraft Industry of the Middle Dnieper Ukrainians during the Establishment of the Soviet Statehood (Early and Mid-20th Century) - Semenova, Oksana (Ukraïnoznavstvo (Naukovo-doslidnyĭ instytut ukraïnoznavstva : 2014-), 2019)
The article is devoted to the transformation of the tanning handicraft industry in the conditions of establishment and further development of the Soviet statehood in the early and mid-twentieth century. The author examines relations between manufacturers, customers and controlling authorities, and also focuses on a new image of a craftsman – not a manufacturer of goods and a good master but a social “enemy” due to class and wealth disparities. A number of legislative documents regulating handicraft tanning industry in 1919–the 1950s are described, and such new forms of labor organization as co-operative craft societies and workshops, labor communities are considered. The author reveals that poor craftsmen used to be the most active in cooperation, while wealthy masters opposed to this process. The masters’ long-established strive to exercise their personality was pushed out by such new values as collective labor, collective property, etc. It is established that high taxation and almost complete monopolization of rawstock by the state, as well as total control over the tanning handicraft industry, led to illegal manufacturing. Soviet authorities used different ways to disclose and punish “shadow” craftsmen: persecution, stigmatizing as “kurkul” and “speculator”, deprivation of civil rights, detention under arrest, confiscation of property, equipment, raw materials, etc. However, the insufficient produce of the state tanning and leather industry raised demands for the handicraft goods. For this reason, the illegal tanning handicraft industry had existed in some regions of the researched territory till the 1960s. The author emphasizes that illegal handicraft industry appeared to be for craftsmen and their families not only the way to survive but also a particular form of opposition to the state policy aimed to remove private manufacturers from the state economic sector.